2018
DOI: 10.1136/archdischild-2017-313864
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delivered tidal volume on the occurrence of intraventricular haemorrhage in preterm infants during positive pressure ventilation in the delivery room

Abstract: High V delivery during mask PPV at birth was associated with brain injury. Strategies to limit V delivery during mask PPV should be used to prevent high V delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 52 publications
1
39
2
Order By: Relevance
“…We have demonstrated that not only high EtCO 2 levels during resuscitation in the delivery suite were associated with IVH development but also inflations resulting in larger tidal volumes and lower EtCO 2 levels [3]. Those findings were subsequently confirmed by Mian and colleagues who found that tidal volumes in excess of 6 ml/kg were associated with cerebral damage in the neonatal period [8]. A further aim, therefore, of this study then was to test the hypothesis that infants exposed to the largest fluctuations in EtCO 2 levels during resuscitation in the delivery suite would be at greatest risk of developing an IVH.…”
Section: Introductionsupporting
confidence: 54%
“…We have demonstrated that not only high EtCO 2 levels during resuscitation in the delivery suite were associated with IVH development but also inflations resulting in larger tidal volumes and lower EtCO 2 levels [3]. Those findings were subsequently confirmed by Mian and colleagues who found that tidal volumes in excess of 6 ml/kg were associated with cerebral damage in the neonatal period [8]. A further aim, therefore, of this study then was to test the hypothesis that infants exposed to the largest fluctuations in EtCO 2 levels during resuscitation in the delivery suite would be at greatest risk of developing an IVH.…”
Section: Introductionsupporting
confidence: 54%
“…Moreover, although several studies have demonstrated CC+SI can provide adequate V T , relatively high distending pressure may cause higher V T [18,31,32]. Therefore, clinicians should be aware of the V T used during PPV and deliver <6-8 mL/kg, particularly in very preterm infants [17,25,31]. In this study, the delivered V T was significantly greater in piglets resuscitated with CC+SI_PIP_30, shown to cause brain inflammation and injury in several animal studies [33][34][35].…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, a recent observational study in preterm infants <29 weeks' gestation observed a four-fold increase in intraventricular hemorrhage in infants ventilated even with a V T >6 mL/kg [17]. Taken together, these studies highlight the link between high V T delivery and the progression of brain injury.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Preclinical studies showed that high tidal volumes adversely affect the cardiopulmonary haemodynamics and even can cause lung27 28 and brain injury 6 29. A recent clinical study30 confirmed the danger of high tidal volumes, as they found more intraventricular haemorrhages in infants receiving tidal volumes >6 mL/kg.…”
Section: Cpap or Ppv Via Facemask When Breathing Is Insufficient In Vmentioning
confidence: 86%